Decision-making depends on language: A meta-analysis of the Foreign Language Effect. Issue 4 (2nd August 2022) - Del Maschio, Nicola; Crespi, Federico; Peressotti, Francesca; Abutalebi, Jubin; Sulpizio, Simone
Abstract: In the present meta-analysis, we investigated the robustness and the magnitude of the Foreign Language Effect (FLE) – that is, the putative effect of language context (native versus foreign language) on decision-making. We also investigated whether the FLE is moderated by language experience – measured by second language age of acquisition and proficiency – or by methodological choices – the types of decision problems adopted, the presentation modality of the tasks administered, and the perspective in which problems are framed. Our results showed a reliable FLE, which was not moderated by language experience or methodological choices. We discuss our findings in relation to available theories of FLE, and indicate possible future directions to improve our understanding of the interplay between bilingualism and decision-making.